Preparatory Stage of Immunization-Free Experimental Production in “Lohmann Lsl Classic” Chicks - Jumanazarov, A. S. (American Journal of Biodiversity, 2025)
This study is aimed at evaluating zoohygienic and technological factors during the initial stage of rearing and keeping Lohmann LSL Classic chicks under experimental conditions. On March 28, 2024, 70-day-old chicks were transported from the Ilonsoy Lohmann poultry farm to the vivarium of Samarkand State University of Veterinary Medicine, Livestock and Biotechnology. During the experiment, the birds were not vaccinated against infectious diseases and were kept under natural immunity conditions. The chicks were housed in a room with an area of 15 m², where the ambient air temperature was maintained at 30 °C, while the temperature under infrared lamps ranged from 35 to 36 °C. The initial average live body weight was 36.6 g. Feeding was carried out using the ad libitum method, taking into account the high egg-laying potential of the breed.